Gender differences in nutrition knowledge, attitude, and practice among elderly people - Chih-Ping Li (International Journal of Management, Economics and Social Sciences (IJMESS), 2017)
Malnutrition is an important public health concern among elderly people. According to the WHO, malnutrition may be a contributing factor to the development of cardiovascular and cerebrovascular disease, diabetes, osteoporosis, and cancer among others. Prior research documents that nutrition knowledge deficits and poor attitude and practices are prevalent in elderly Taiwanese. The purpose of this study was to identify several factors (e.g. age, education, marital status, money for living expense, physical and mental health) that impact on nutrition knowledge, attitude and dietary practice among elderly Taiwanese men and women. Data from the 2004-2008 Nutrition and Health Survey in Taiwan (NAHSIT) (Data file: D00090) in the Survey Research Data Archive, Center for Survey Research, Research Center for Humanities and Social Sciences, Academia Sinica was used for analysis. The participants were 258 elderly people with an age range of 72.88Â±6.09. Multiple regression tests were incorporated to examine predictors affecting nutrition knowledge, attitude, and dietary practice of the elderly males and elderly females. The results did not identify any key factors that influence nutrition knowledge for older male and female people. Age was noted to be an independent predictor in nutrition attitude for male but not female elderly people. Both education and marital status had an effect on nutrition attitude and dietary practice for older men. On the other hand, only education affected nutrition attitude and dietary practice for older women. Mental health was an independent predictor for nutrition attitude. Money for living expenses had a significant effect on nutritional dietary practices for older women.
Keywords: 330; Elderly people; gender difference; nutrition knowledge; attitude; practice